EMG analysis of facial muscles exercise using oral cavity rehabilitative device - Ibrahim, F.; Chae, J.H.; Arifin, N.; Zarmani, N.M.; Cho, J. (2007)
This study presents the analysis of surface electromyography (sEMG) of facial muscles in different age categories. The analysis was evaluated when the subjects performed the gripping oral exercise device in a static contraction. The sEMG measurements were taken at four positions; Orbicularis Oris Superiors Left (OOSL) and Right (OOSR), Orbicularis Oris Inferiors Left (OOIL) and Right (OOIR) using TeleMyo2400T. There are only 4 female subjects participated in the study which is divided into 2 Groups: Groups 1 and 2 with mean age of 47.5 and 23 years old, respectively. The findings indicate that the mean and median frequencies of sEMG activity recorded from both left and right of OOS and OOI muscles showed decreasing trend from the beginning until the end of the static contraction sessions. The power spectral density of sEMG signal on those muscles for both groups is in the range of 19 to 45 Hz. Â© 2006 IEEE.